Government's Strategies In The Development Of The Conscience Of Society Based On Stunting Revolution Program In Lampung Province - Arini, Isti; Suhandi (Universitas Islam Negeri Raden Intan Lampung, 2024)
The aim of this research is its significance in providing scientific and practical contributions to the government's strategy in developing public awareness for handling stunting in Lampung Province. This research method is a literature review which uses qualitative data and is described descriptively. The data sources for this research were obtained from references such as journals, books and other written sources, especially strategic data from the Ministry of Health for Lampung province for 2019-2024. Research results: The Lampung Provincial Government adopted various strategies to develop public awareness regarding stunting. This strategy includes an educational campaign involving relevant parties, such as health workers and teachers, to convey accurate information about the importance of nutrition and healthy feeding practices. Training and counseling are also carried out regularly to provide the public with a deeper understanding of stunting and how to prevent it. The use of effective communication media, such as social media, posters, brochures and educational videos, is an important means of conveying messages related to stunting to the public. Apart from that, active community participation in program planning and implementation is also emphasized, so as to create good cooperation between the government and the community in overcoming stunting in Lampung Province.